PENGATURAN CRYPTOCURRENCY (MATA UANG KRIPTO) SEBAGAI ALAT PEMBAYARAN TRANSAKSI DI INDONESIA - Subakti, I Putu Sandhi; Putra, Made Aditya Pramana (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 8 (2024), 2025)
The purpose of writing this article is to find out how cryptocurrency is regulated as a means of payment for transactions in ndonesia and what are the legal consequences of cryptocurrency as a means of payment for transactions in Indonesia. Writing this article uses normative legal research methods with a statutory approach and a conceptual approach. The results of writing this article explain that cryptocurrency has (2) two uses, namely as an investment commodity and a medium of exchange. As a medium of exchange, cryptocurrency has currency characteristics because it can be accepted as a means of payment in several countries. Based on Article 34 of Bank Indonesia Regulation no. 18/40/PBI/2016 concerning the Implementation of Payment Transaction Processing states that the Implementation of Payment Transaction Processing is prohibited from processing payment transactions using cryptocurrency. Positive law in Indonesia does not fully regulate the prohibition on the use of cryptocurrency as a means of payment for transactions. So this needs to be studied more comprehensively regarding regulations and legal consequences if cryptocurrency is used as a payment instrument in Indonesia.